1979
DOI: 10.1007/bf02663046
|View full text |Cite
|
Sign up to set email alerts
|

Toxic weed seed contaminants in soybean processing

Abstract: Soybeans are subject to potential contamination from toxic weed seeds during harvest, transportation and storage. The more common foreign seeds include those from jimsonweed, cocklebur, nightshade, cowcockle, corncockle, morning glory, castor, pokeweed, and crotalaria. This review addresses itself to the chemistry and toxic principles of these contaminants. Since jimsonweed seeds are probably the most toxic and most prevalent contaminant of soybeans, they are discussed in greatest detail. A gas liquid Chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…21 Every morphological part of the Datura plants contains belladonna alkaloids and the concentration will vary depending on the species, climate, rainfall, season of the year, and the part of the plant that is involved in the exposure. 29 In decreasing order, the belladonna alkaloid content is generally the greatest in the petioles (flowers), stem, fruit (seeds), leaves, and roots. 29 When Datura is used for substance-abuse purposes, ingestion (usually of the seeds) is the most common route of exposure.…”
Section: Mechanisms Of Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…21 Every morphological part of the Datura plants contains belladonna alkaloids and the concentration will vary depending on the species, climate, rainfall, season of the year, and the part of the plant that is involved in the exposure. 29 In decreasing order, the belladonna alkaloid content is generally the greatest in the petioles (flowers), stem, fruit (seeds), leaves, and roots. 29 When Datura is used for substance-abuse purposes, ingestion (usually of the seeds) is the most common route of exposure.…”
Section: Mechanisms Of Toxicitymentioning
confidence: 99%
“…29 In decreasing order, the belladonna alkaloid content is generally the greatest in the petioles (flowers), stem, fruit (seeds), leaves, and roots. 29 When Datura is used for substance-abuse purposes, ingestion (usually of the seeds) is the most common route of exposure. 30 The alkaloids are synthesized in the roots and then stored in vacuoles throughout the plant.…”
Section: Mechanisms Of Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, atropine is more abundant in D. stramonium whereas scopolamine is prevalent in D. ferox . D. stramonium seeds found as contaminants in a soybean crop contained atropine, scopolamine and total alkaloid levels of 0.29%, 0.05%, and 0.34%, respectively, corresponding to an scopolamine:atropine ratio of 15:85 [ 30 ]. In another study, the scopolamine:atropine ratio found in D. ferox seeds was found to be 98:2 [ 31 ].…”
Section: Tropane Alkaloidsmentioning
confidence: 99%
“…There are no recent reports on the effect of ensiling on levels of TAs in contaminated silage. However, List and Spencer (1979) reported that livestock in the United States have perished as a result of consuming Jimson weed plants present in hay or silage, suggesting that the ensiling process does not destroy the TAs.…”
Section: Food and Feed Processingmentioning
confidence: 99%